Project management the managerial process - Larson, Erik W. 1952- (McGraw-Hill/Irwin series operations and decision sciences, 2011)
This textbook presents a balanced treatment of both the technical and behavioural issues in project management as well as covering a broad range of industries to which project management principles can be applied.